CALCULATION OF MAGNETIC CIRCUIT OF SINGLE-PHASE INDUCTION MOTOR WITH DECOMPOSED POLES - V. S. Malyar; L. Yu. Glukhivskyi; A. V. Malyar; D. P. Grechyn; R. Gavdyo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
An equivalent circuit of single-phase induction motor with decomposed poles has been proposed in the paper. It gives the possibility to calculate magnetic field of the machine under known values of loop currents. High level and detailed presentation of magnetic core makes it possible to determine electromagnetic parameters and investigate an influence of motor geometry on its behavior under steady state and dynamic modes.